Reasons for Buyer’s choices towards Electronic Means of Transportation in India: An Empirical Study in the context of ESG (Environment, Social, Government) Marketing Model - Chheda, Dr.Kajal (The journal of contemporary issues in business and government, 2023)
The electric cars are the environment-friendly means of transportation. India is a significant potential market for the use of electric vehicles. Hence the Indian government aspires to be the top fully electric producer by 2030. Nearly every automotive manufacturer in the world already produces at least one electric vehicle model, and the adoption of electric vehicles is rising quickly across the board. The Indian government has unveiled several fresh initiatives to support the producers of electric cars, which would undoubtedly result in a pollution-free environment. Despite being a complicated and lengthy road, it is certainly attainable with a thorough strategy approach. New initiatives must be implemented to increase the acceptability of electric vehicles, while steps must be taken to prevent the further uptake of gasoline-powered cars. Sample of 248 buyers were considered for the study survey to know the reasons for buyer's choices towards Electronic Means of Transportation in India and the impact of ESG (Environment, Social, Government) Marketing Model. Electronic Means of Transportation Lowers the risks to local public health connected with those emission, greenhouse gas emission and Governments offers state federal subsidies on electric vehicles are some of the reasons for buyer's choices towards Electronic Means of Transportation in India. The study concludes that there is significant impact of ESG (Environment, Social, and Government) Marketing Model on Buyer's choices towards Electronic Means of Transportation.